A portable digital multipulse NQR spectrometer for the study of the sensory properties, structure and defects in layered semiconductors - Samila, Andriy; Hotra, Oleksandra; Politansky, Leonid (IEEE, 2020)
The structure of a digital pulse coherent NQR spectrometer with a minimum number of functional units for the investigation of GaSe and InSe layered semiconductor crystals is proposed. The feature of the proposed measuring setup is the implementation of all algorithms of digital processing and signal synthesis in the basis of one statically-configured FPGA EP4CE15E22C8. The digital 48-bit frequency synthesizer provides the formation of carrier frequency oscillations, which fill of the excitation pulses in the NQR frequencies range 1 – 50 MHz (isotopes 14N, 69Ga, 71Ga, 113In, 115In, and others). Reliable gating of the receiver in the pauses between the excitation pulses (up to 100 dB for the carrier frequency) is ensured by a circuit diagram of three stages of the same type on double gate field-effect transistors.
Keywords: radio spectrometer; NQR; transient process; FPGA